Next‐generation QTL mapping: crowdsourcing SNPs, without pedigrees. Issue 15 (25th July 2013) - Edwards, Scott V.
Abstract : For many molecular ecologists, the mantra and mission of the field of ecological genomics could be encapsulated by the phrase 'to find the genes that matter' (Mitchell‐Olds2001 ; Rockman2012 ). This phrase of course refers to the early hope and current increasing success in the search for genes whose variation underlies phenotypic variation and fitness in natural populations. In the years since the modern incarnation of the field of ecological genomics, many would agree that the low‐hanging fruit has, at least in principle, been plucked: we now have several elegant examples of genes whose variation influences key adaptive traits in natural populations, and these examples have revealed important insights into the architecture of adaptive variation (Hoekstra et al .2006 ; Shapiro et al .2009 ; Chan et al .2010 ). But how well will these early examples, often involving single genes of large effect on discrete or near‐discrete phenotypes, represent the dynamics of adaptive change for the totality of phenotypes in nature? Will traits exhibiting continuous rather than discrete variation in natural populations have as simple a genetic basis as these early examples suggest (Prasad et al .2012 ; Rockman2012 )? Two papers in this issue (Robinson et al .2013 ; Santure et al .2013 ) not only suggest answers to these questions but also provide useful extensions of statistical approaches for ecological geneticists to study the genetics of continuous variation in nature. Together these papers, by the same research groups studying evolution in a natural population of Great Tits ( Parus major ), provide a glimpse of what we should expect as the field begins to dissect the genetic basis of what is arguably the most common type of variation in nature, and how genome‐wide surveys of variation can be applied to natural populations without pedigrees.